2022
DOI: 10.1002/cptc.202200156
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Iron‐Doped Carbon Dots and Their Application in Photocatalytic Reduction of Carbon Dioxide

Abstract: Photocatalytic carbon dioxide (CO2) reduction technology is considered a promising approach to alleviate greenhouse gas emissions in the earth's atmosphere. Carbon dots (CDs), which possess good optical properties, are of keen interest in the field of photocatalysis. Iron (Fe), a transition metal element with vacant 3d orbital that contributes to the electron‐transfer process, is a promising metal dopant for CDs that allows for the preparation of multifunctional CDs. Fe‐doped carbon dots (Fe−CDs) were synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Lu et al ( 2015 ) reported better photocatalytic activity of zinc-porphyrin modified GQDs compared to zinc-porphyrin towards the degradation of methylene blue (MB) under visible-light. On the other hand, Dang et al ( 2022 ) used Fe-doped CQDs to generate methanol by CO 2 reduction. A three-fold increase in photocatalytic activity of S and N co-doped CQDs with TiO 2 NPs was observed towards acid red 88 degradation (Rahbar et al 2019 ).…”
Section: Limitations and Future Research Prospects Of Carbon-based Qu...mentioning
confidence: 99%
“…Lu et al ( 2015 ) reported better photocatalytic activity of zinc-porphyrin modified GQDs compared to zinc-porphyrin towards the degradation of methylene blue (MB) under visible-light. On the other hand, Dang et al ( 2022 ) used Fe-doped CQDs to generate methanol by CO 2 reduction. A three-fold increase in photocatalytic activity of S and N co-doped CQDs with TiO 2 NPs was observed towards acid red 88 degradation (Rahbar et al 2019 ).…”
Section: Limitations and Future Research Prospects Of Carbon-based Qu...mentioning
confidence: 99%
“…Consequently, the Fe-CDs showed 2.6-times greater photocatalytic reduction ability (CO 2 to methanol) compared to the undoped CDs. 110 Zhang et al 111 used the traditional Chinese herb mulberry together with MgCl 2 -$6H 2 O to synthesize Mg-CDs through the HT technique (200 °C, 10 h). The Mg-CDs were applied for in vitro osteoblastic differentiation and matrix mineralization.…”
Section: Heteroatom Dopingmentioning
confidence: 99%